Effect of Collaborative Learning on Students’ Communication Skills and Reasoning Skills - Dr Fahad Naveed Kausar (Social Science Review Archives, 2025)
Collaborative learning enhances students’ communication and reasoning skills by fostering dialogue, critical thinking, and problem-solving through peer interaction. The objectives of the research were to investigate the level of Collaborative Learning on Students’ Communication Skills and Reasoning Skills, and to examine the relationship and influence of Collaborative Learning on Students’ Communication Skills and Reasoning Skills at university level. The nature of this research was descriptive, and quantitative data collection procedures were employed to conduct it. Quantitative research is grounded in a positivistic philosophical framework or paradigm. The study population comprised all public and private universities in the Lahore district. To ensure proper representation, a sufficient sample of students was included in the study. To collect data, a questionnaire was employed. The tool was validated through expert review and pilot testing. The collected data was analyzed using SPSS, with descriptive statistics (mean and standard deviation) and inferential statistics (Pearson r and multivariate analysis) applied to achieve the study’s objectives. The findings of the study revealed that there was highly significant relationship an influence of Collaborative Learning on Students’ Communication Skills and Reasoning Skills at university level. It is recommended that Integrate structured collaborative activities into curricula to systematically enhance both communication and reasoning skills. Design problem-based and inquiry-oriented tasks that require students to engage in critical thinking, analysis, and evidence-based reasoning during group work.